Minimally Invasive Inlay Prosthesis Unicompartmental Knee Arthroplasty for the Treatment of Unicompartmental Osteoarthritis: A Prospective Observational Cohort Study with Minimum 2-Year Outcomes and up to 14-Year Survival - Scholes, Corey; Ebrahimi, Milad; Field, Clarice; Farah, Sami; Kerr, Dennis; Kohan, Lawrence (The Journal of Knee Surgery, 2019)
There are limited medium-term outcome data available for the Repicci II device in unicompartmental knee arthroplasty (UKA). The purpose of this study was to report the medium-term (minimum 2 years) patient-reported outcomes and long-term (up to 14 years) procedure survival in a consecutive series of patients undergoing an inlay prosthesis UKA (Repicci II) at an independent orthopaedic clinic. Patients presenting with medially localized unicompartmental knee osteoarthritis and meeting the criteria appropriate for UKA were recruited to a clinical patient registry at the time of presentation. A cemented unicompartmental prosthesis (Repicci II) was implanted using minimally invasive techniques with rapid postoperative mobilization. Patients were asked to complete patient-reported outcomes preoperatively and annually postoperatively. A procedure list was cross-matched with the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR), and an analysis of procedure survival was performed with comparison to the national data for UKA. Data from a cohort of 661 primary medial compartment UKA procedures performed in 551 patients over a 15-year period were extracted from the clinical patient registry. Significant improvements were maintained in general health, disease symptoms, pain, and function at an average follow-up of 9 years compared with preoperative data. Threshold analysis revealed that >65% of patients exceeded Patient Acceptable Symptom State at the latest follow-up, with >80% within or exceeding age-matched norms for general health. Cumulative revision rate was significantly lower than that reported for UKA in the AOANJRR at up to 13 years follow-up. This series represents a lower cumulative revision rate than previously reported, with >65% of patients reporting satisfactory functional outcomes at an average of 9 years from surgery. Surgical options for treating unicompartmental knee osteoarthritis could include UKA as a viable alternative; however, clear definitions of procedure success and its overall cost–benefit ratio in the context of ongoing management of knee osteoarthritis remain to be elucidated.
Keywords: unicompartmental knee arthroplasty; patient-reported outcomes; long-term follow-up